Beginning of a psychologist’s professional career: Expectations regarding education - Lepeškienė, Vitalija; Bulotaitė, Laima (Psichologija, 2010)
The article deals with the issue of the expectations of the freshmen psychology students regarding the possible impact of the studies on their personal and professional life. Since students’ subjective expectations were the issue of interest, the Q-methodology was used in the research. Forty-eight students (41 females and 7 males) sorted 48 statements answering the question: “How, in your opinion, your studies will affect your future personal and professional life?” The statements were formulated to create a representative sample of the ideas about the influence of the psychologist’s profession on students’ personality qualities, relationships, skills, values and life in general. The statements were meant to represent influences on four levels (intrapersonal, interpersonal [with a the closest people], professional and interpersonal [with wider social environment]) and three areas – knowledge, skills and values. Forty-eight complete Q-sorts were factor analyzed using Q-method factor analysis program for Q methodology, version 2.11; 40 subjects (83%) defined four factors (groups of students) representing different expectations of the students. The views of the factors were briefly expressed as follows: Group I (4 subjects, 10.0%): knowledge is not the most important thing. I want to better understand myself and to grow; Group II (15 subjects, 37.5%): there is no need for me to change. Most important is to acquire professional skills; Group III (8 subjects, 20.0%): it doesn’t matter what kind of a professional I shall become. Solving my own problems is what really matters; Group IV (13 subjects, 32.5%): respect for a human being is the most important value. Work and personal life have nothing in common. Thus, the research revealed different expectations of the students regarding the influence of the studies. A rather substantial percentage of freshmen students expect the studies to help clarify their motifs, resolve inner contradictions, help in the process of personal growth and change in desired direction. Some students have unrealistic expectations regarding the possibility to separate personal and professional life. In order to help the students meet their expectations, the program of training future psychologists must be reoriented so that the students not only could acquire knowledge and skills, but also expand their self-awareness.